Body mass index, fitness and physical activity from childhood through adolescence. Issue 2 (18th July 2012) - Pahkala, Katja; Hernelahti, Miika; Heinonen, Olli J; Raittinen, Päivi; Hakanen, Maarit; Lagström, Hanna; Viikari, Jorma S A; Rönnemaa, Tapani; Raitakari, Olli T; Simell, Olli
Abstract : Background: Obesity, sedentary lifestyle and poor cardiorespiratory fitness in childhood may increase the risk of health problems later in life. Purpose: The authors studied the association of early childhood weight status with cardiorespiratory fitness and leisure-time physical activity (LTPA) in adolescence. The stability and associations of LTPA and fitness from childhood through adolescence were also studied. Methods: Body mass index (BMI) was assessed annually since birth in a prospective, longitudinal study. The mean BMI between ages 2 and 7 years indicated weight status at preschool age. Fitness was studied with a shuttle run test at age 9 and with a maximal cycle ergometer test at age 17. The same questionnaire was used to assess LTPA at age 9, 13 and 17. Complete data on preschool BMI, LTPA at ages 13 and 17 and fitness at age 17 years was provided by 351 children, while fitness and LTPA data were available for 74 children at ages 9 and 17. Results: Preschool BMI was inversely associated with fitness in adolescence independently of adolescent LTPA (p=0.0001). Children who had a high preschool BMI but whose weight status was reduced in adolescence had similar fitness in adolescence as the children with a persistently low BMI. Regardless of the fitness level in childhood, the children whose LTPA increased between age 9 and 17 had a similar adolescent fitness level as persistently active subjects. Conclusions: It is important to maintain a healthy body weight and a physically active lifestyle from very childhood through adolescence to improve fitness during adolescence.